2016
DOI: 10.4238/gmr15048843
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of the genetic diversity of Gymnospermium microrrhynchum in Korea

Abstract: ABSTRACT. Gymnospermium microrrhynchum (Berberidaceae) is an ephemeral perennial herb with a limited distributional range in the Baekdudaegan mountain areas of the Korean Peninsula, and is designated a rare plant by the Korean Forest Service. Information about its genetic variation and structure is important for developing successful conservation strategies. To investigate the genetic variation within and among seven G. microrrhynchum populations, random amplified polymorphic DNA data were obtained for 207 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…Similar results were found for population genetic diversity, where mean H e values resulted almost identical (G. eddae = 0.187; G. microrrhyncum = 0.188). At species level, however, genetic diversity in G. eddae resulted lower (H e = 0.210) than in G. microrrhyncum (H e = 0.349), likely due to the much larger range of the latter species and the genetic differentiation among its populations on the mountains of the Korean peninsula (Lee et al 2016). Gymnospermium microrrynchum is in fact the most isolated species of the genus, from both a geographical and phylogenetic point of view (Loconte and Estes 1989;Barina et al 2017;Rosati et al 2019a).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similar results were found for population genetic diversity, where mean H e values resulted almost identical (G. eddae = 0.187; G. microrrhyncum = 0.188). At species level, however, genetic diversity in G. eddae resulted lower (H e = 0.210) than in G. microrrhyncum (H e = 0.349), likely due to the much larger range of the latter species and the genetic differentiation among its populations on the mountains of the Korean peninsula (Lee et al 2016). Gymnospermium microrrynchum is in fact the most isolated species of the genus, from both a geographical and phylogenetic point of view (Loconte and Estes 1989;Barina et al 2017;Rosati et al 2019a).…”
Section: Discussionmentioning
confidence: 92%
“…Using RAPDs allowed comparing results with those concerning G. microrrhyncum from South Korea, which was investigated with the same primers (Lee et al 2016). As found in G. microrrhyncum, the highest and lowest percentages of polymorphic bands (PPB) in G. eddae were detected with the primers respectively (Table 2).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, they found that the desert xerophytes of Berberidaceae in southwestern Asia arose as a result of changes in climate aridity at different times; Bongardia separated from its closest relatives after 46.5 ± 3.6 million years, and Leontice separated from Gymnospermium after 10.3 ± 3.2 million years. The genetic diversity of the rare endemic species Gymnospermium micror rhynchum (S. Moore) Takht., which has a limited distribution area in the mountainous regions of the Korean Peninsula, has also been studied to develop successful strategies for its conservation [19]. Some taxonomists continued to revise the size of the genus Gymnospermium at the western border of its range, i.e.…”
Section: Introductionmentioning
confidence: 99%